Class I major histocompatibility complex-restricted T lymphocyte recognition of the influenza hemagglutinin. Overlap between class I cytotoxic T lymphocytes and antibody sites (The Rockefeller University Press, 1989)
The influenza hemagglutinin is a critical regulator of disease expression during influenza virus infection and serves as a major target for the host immune response to this pathogen. In this report, we have analyzed an immunodominant site on the hemagglutinin (residues 202-221) recognized by murine class I MHC-restricted T lymphocytes. This analysis has revealed evidence for the duplication of a T cell recognition site within the region 202-221. We have also identified critical amino acids necessary for class I-restricted T cell recognition within these two epitopes. In addition, we provide evidence that a site on the influenza hemagglutinin recognized by neutralizing antibody directly overlaps with an epitope recognized by class I MHC- restricted CTL.